Recent progress in self-supported nanoarrays with diverse substrates for water splitting and beyond. (August 2021) - Xiang, Q.; Wang, J.; Miao, Q.; Tao, P.; Song, C.; Shang, W.; Deng, T.; Yin, Z.; Wu, J.
Abstract: Electrocatalytic water splitting plays a paramount importance role in hydrogen production as a green renewable energy technology. Therefore, development of highly efficient and durable electrocatalysts for oxygen evolution reaction and hydrogen evolution reaction has gained great interest. Self-supported nanoarray electrocatalysts are attracting intense attention owing to larger active areas and lower reaction overpotential than the freestanding particles. Herein, the recent progress with regard to self-supported nanoarray electrocatalysts for water splitting is systematically overviewed, with a special focus on the morphology including 1D, 2D, and heterostructure nanoarrays, as well as the design and preparation strategy of the substrates. Furthermore, the challenges and opportunities of self-supported nanoarray electrocatalysts for water splitting are also discussed. Moreover, the promising application of self-supported nanoarray electrocatalysts in CO2 reduction reaction and nitrogen reduction reaction is also investigated. Graphical abstract: Schematic of self-supported nanoarray electrocatalysts on diverse substrates for water splitting. Reproduced with permission from Refs. [1–13 ]. Image 1